The Role of Learning Support and Chat-Sessions in Guided Internet-Based Cognitive Behavioral Therapy for Adolescents With Anxiety: A Factorial Design Study - Berg, Matilda; Rozental, Alexander; de Brun Mangs, Josefine; Näsman, Maja; Strömberg, Karin; Viberg, Linn; Wallner, Erik; Åhman, Hanna; Silfvernagel, Kristin; Zetterqvist, Maria; Topooco, Naira; Capusan, Andrea; et al. (Frontiers in Psychiatry, 2020)
Abstract Background: Increased awareness of anxiety in adolescents emphasises the need for effective interventions. Internet-based cognitive behaviour therapy (ICBT) could be a resource-effective and evidence-based treatment option, but little is known about how to optimize ICBT or which factors boost outcomes. Recently, the role of knowledge in psychotherapy has received increased focus. Further, chat-sessions are of interest when trying to optimize ICBT for youths. This study aimed to evaluate the role of learning support and chat-sessions during ICBT for adolescent anxiety, using a factorial design. Method: A total of 120 adolescents were randomised to one of four treatment groups, in a 2x2 design with two factors: with or without learning support and/or chat-sessions. Results: Anxiety and depressive symptoms were reduced (Beck Anxiety Inventory- BAI; Cohen’s d =0.72; Beck Depression Inventory- BDI; d =0.97). There was a main effect of learning support on BAI (d =0.37), and learning support increased knowledge gain (d =0.42). There were no main effects or interactions related to the chat-sessions. Treatment effects were maintained at six-months, but the added effect of learning support had by then vanished. Conclusion: ICBT can be an effective alternative when treating adolescents with anxiety. Learning support could be of importance to enhance short-term treatment effects, and should be investigated further.